Community Empowerment in Tourism Management at Kampung Flory,Tridadi Village, Sleman Regency, Yogyakarta - Dewi, Roels Ni Made Sri Puspa; Yutsi, Surya Pratama (Media Wisata, 2024)
Community empowerment is needed in every management of the tourism industry. Kampung Flory has been developed for a long time and benefits the community. The tourist attractions that Kampung Flory owns are quite diverse and offer many choices to tourists. This study aims to examine community empowerment in the management of destinations in Kampung Flory followed by organizing a management model according to the tourism institutions in Kampung Flory. This study uses a quantitative approach. Methods of data collection are carried out by observation, questionnaires, and literature study with the number of respondents being 123 people. Data analysis methods using descriptive statistical analysis methods assisted by a Likert scale. The results of this study indicate that social empowerment and economic empowerment for the people of Kampung Flory are good. The average score of all these variables is 3.56 indicating that the community strongly agrees with empowerment because from the initial stage to the tourism development stage in Kampung Flory is carried out all by the community. The form of community empowerment in Kampung Flory is in the form of community involvement in the management of tourism objects such as recruitment as labor and opening a business in the tourist area of Kampung Flory.